KOMPONEN DAYA TARIK AGROWISATA TAMAN EDELWEIS - Sukendar, Ni Made Classia; Setiawan, I Gede Bagus Dera; Arisena, Gede Mekse Korri (Universitas Galuh, 2023)
The Edelweiss Park agrotourism is a leading agrotourism developed as a tourist attraction in Karangasem Regency. The component of agro-tourism attraction is essential to note for the sustainability of Edelweiss Park agrotourism. Attributes are one of the components of the agrotourism attraction of Edelweiss Park which consists of attractions, facilities, accessibility, and hospitality. This study aimed to look at the types of attractions, availability of facilities, accessibility, and the level of hospitality in Taman Edelweiss agrotourism. This research was carried out at the Edelweiss Park agrotourism, Banjar Dinas Temukus, Besakih Village, Rendang District, Karangasem Regency. The sampling technique used was purposive with a sample of 100 visitor respondents who had finished their activities in Taman Edelweiss agrotourism. The data analysis technique used is descriptive quantitative and descriptive qualitative analysis techniques. The results showed that the respondents strongly agreed and agreed with the types of attractions provided by Taman Edelweiss agrotourism. Respondents also strongly agreed and agreed with the facilities provided by Taman Edelweiss agrotourism. Furthermore, respondents felt they decided, were neutral, and even disagreed with the accessibility to Taman Edelweiss agrotourism. Finally, the respondents agree with the level of hospitality in Edelweiss Park agrotourism.